Design, synthesis, cytotoxicity evaluation, and molecular docking studies of 1,3,4 oxadiazole substituted 1,4-naphthoquinone derivatives - Besan M.; Gautam M.K.; Shrivastava S.K. (My University, 2025)
In this manuscript we have designed and synthesized 1,4-Naphthoquinone analogs substituted with 1,3,4 Oxadiazolenucleus.The synthesized compound (M1-M14) were characterized using the different analytical technique1H NMR,13C NMR, FTIR, Mass spectroscopy, melting point, elemental analysis and further subjected for the evaluation of their anticancer activity using MCF-7, Hela and HepG2 cancer cell lines. The compound M-5 was found to exhibit most potent cytotoxicity against cancer cell lines i.e. HeLa (IC50 =10.76 ± 0.11 μM), MCF-7 (IC50 = 9.30 ± 0.14 μM) and HepG2 (IC50 = 11.93 ± 0.38μM). Compound M-5 has also shown potent tyrosine kinase inhibitory activity with IC50 = 1.53 ± 0.05 μM. Moreover, molecular docking has exposed that compound M-5 has strong binding affinity to the active site of tyrosine kinase. These results give promising beginning stages to assist in the improvement of novel and powerful anticancer agents. © 2019, Association of Biotechnology and Pharmacy. All rights reserved.